Can anticipated regret promote rationality? The influence of anticipated regret on risk aversion and choice satisfaction - Liu, Jing; Liu, Haiyan (Frontiers in Psychology, 2025)
ObjectiveThis research examines the impact of anticipated regret on decision-making under risk, focusing specifically on its role in promoting risk aversion and enhancing choice satisfaction.MethodsThree studies were conducted to systematically investigate the effects of anticipated regret. In Study 1, the Balloon Analog Risk Task (BART) was used to manipulate the presence or absence of anticipated regret. Study 2 introduced individual differences in risk preference to examine how this trait interacts with anticipated regret in shaping risk-taking behavior. Study 3 added a time pressure condition to explore how anticipated regret functions under varying decision-making constraints.ResultsStudy 1 showed that anticipated regret significantly increased risk-averse behavior and improved choice satisfaction. In Study 2, both anticipated regret and individual risk preference influenced risk-taking, but only anticipated regret had a consistent positive effect on satisfaction. No significant interaction was found between the two variables. Study 3 revealed that participants were generally more risk-averse under time pressure, and the effect of anticipated regret on risk avoidance was attenuated in high-pressure conditions. However, its positive influence on satisfaction remained stable across conditions.ConclusionAnticipated regret consistently influenced both risk-taking behavior and choice satisfaction across different individual dispositions and situational conditions, highlighting the stable and significant role of prospective emotions in decision-making under risk.